2008
DOI: 10.1021/ic702325m
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Luminescent Properties of Micro- and Nanosized Particles of Lanthanide Terephthalate Coordination Polymers

Abstract: Reaction in water between rare earth ions (Ln = Y, La-Tm, except Pm) and the sodium salt of terephthalic acid leads to a family of lanthanide-based coordination polymers of general formula [Ln2(C8H4O4)3(H2O)4] n with Ln = La-Tm or Y. The isostructurality of the compounds with the previously reported Tb-containing polymer is ascertained on the basis of their X-ray powder diffraction diagrams. The coordination water molecules can be reversibly removed without destroying the crystal structure for compounds involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
160
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(174 citation statements)
references
References 46 publications
13
160
1
Order By: Relevance
“…In this crystal structure, there is only one crystallographically independent Tb 3+ ion that occupies a 2i Wyckoff position. This is in agreement with previously reported luminescence studies in which only one metal ion environment with a pseudo C 4 symmetry was observed in the homonuclear [Eu 2 (bdc) 3 26] compound. Powder X-ray diffraction studies showed that in these compounds there is no long-range order or segregation.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In this crystal structure, there is only one crystallographically independent Tb 3+ ion that occupies a 2i Wyckoff position. This is in agreement with previously reported luminescence studies in which only one metal ion environment with a pseudo C 4 symmetry was observed in the homonuclear [Eu 2 (bdc) 3 26] compound. Powder X-ray diffraction studies showed that in these compounds there is no long-range order or segregation.…”
Section: Resultssupporting
confidence: 93%
“…These spectra also show that 312 nm is an efficient excitation wavelength for these compounds. [26] This is an interesting result as far as industrial applications are concerned, because this is a cheap commercially available irradiation wavelength. Therefore, the excitation wavelength was chosen as 312 nm in the following study.…”
Section: Homonuclear Compoundsmentioning
confidence: 89%
See 2 more Smart Citations
“…6 Thermal stability of the luminescent plastic materials are required that Preparations of lanthanide coordination nanoparticles assisted with surface stabilizers have been reported. 14,15 Kimizuka has also successfully reported lanthanide 4 coordination nanoparticles using supramolecular networks. 16 We here focused on characteristic formation of organo-nanoparticles using micelle technique in liquid media, such as preparation of nano scaled organic compounds.…”
Section: Introductionmentioning
confidence: 99%